Transoxiana (Mawaraunnahr) Hanafi Hadith Scholors (muhaddith) Ebu’l-Abbas al-Mustagfiri and his Place in Science of Hadith - Abduganiev, Asilbek (Scientific Journal of Faculty of Theology, 2018)
Abu’l-Abbas al-Müstagfirī (d. 350/432), who was counted as belonging to the Hanafī hadith hafizes of Mavarannehir, was born in Nasaf and completed his scientific development benefiting from various scholars of different regions. Along with that, he has copyrighted nearly 20 works and has educated many students. Müstagfirī, who assumed the oratory of Nasaf passed away in 432 Hijrī by serving the science and Islam. Regarded as “imam”, “fakih” and “hafiz”, Müstagfirī also has important place in the hadith science. In this study, the works of Müstagfirī in the hadith science have been examined. This work has studied scientific, political, social and cultural aspects of the ambient and timeframe in which Müstağfirī lived. Afterwards, the explanations and evaluations of his books were investigated in order to determine the hadith of Mustagfirī. As a result of the study, it can be said that Mustagfirī is a famous hadith and plays an active role for the scholars who follow him.